An iterative algorithm for analysis of coupled structural-acoustic systems subject to random excitations - Zhao, Guo-Zhong; Chen, Gang; Kang, Zhan (Acta mechanica Sinica, 2012)
This paper analyzes the random response of structural-acoustic coupled systems. Most existing works on coupled structural-acoustic analysis are limited to systems under deterministic excitations due to high computational cost required by a random response analysis. To reduce the computational burden involved in the coupled random analysis, an iterative procedure based on the Pseudo excitation method has been developed. It is found that this algorithm has an overwhelming advantage in computing efficiency over traditional methods, as demonstrated by some numerical examples given in this paper.